2024
DOI: 10.3390/ph17010106
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drug Safety in Pediatric and Young Adult Patients with Hemato-Oncological Diseases: A Prospective Study of Active Pharmacovigilance

Anna Parzianello,
Giulia Fornasier,
Valentina Kiren
et al.

Abstract: The acquisition of relevant pediatric clinical safety data is essential to ensure tolerable drug therapies. Comparing the real number of Adverse Drug Reaction (ADR) reports in clinical practice with the literature, the idea of ADR underreporting emerges. An active pharmacovigilance observational prospective study was conducted to assess the safety of oncology pharmacological prescriptions in patients aged 0–24 years at Institute for Maternal and Child Health IRCCS Burlo Garofolo in Trieste and IRCCS CRO Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The challenges in recognizing ADRs in oncology settings are often due to polypharmacy and under-reporting [ 18 , 20 ]. Nonetheless, it is crucial to acknowledge that ADR reporting in oncology settings has shown an upward trend over the years [ 10 , 21 ]. A recent study on PV for oncological prescriptions in patients aged 0–24 showed a significant increase in ADR reports, with off-label prescriptions being 3.4 times more likely to result in ADRs than on-label ones [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The challenges in recognizing ADRs in oncology settings are often due to polypharmacy and under-reporting [ 18 , 20 ]. Nonetheless, it is crucial to acknowledge that ADR reporting in oncology settings has shown an upward trend over the years [ 10 , 21 ]. A recent study on PV for oncological prescriptions in patients aged 0–24 showed a significant increase in ADR reports, with off-label prescriptions being 3.4 times more likely to result in ADRs than on-label ones [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is crucial to acknowledge that ADR reporting in oncology settings has shown an upward trend over the years [ 10 , 21 ]. A recent study on PV for oncological prescriptions in patients aged 0–24 showed a significant increase in ADR reports, with off-label prescriptions being 3.4 times more likely to result in ADRs than on-label ones [ 21 ]. It was also found that 6.3% of prescriptions had errors and 18.2% near-misses, with 35.3% of 133 drug interactions causing ADRs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations